ACCOUNTING IN THE CONDITIONS OF DIGITALIZATION - RUDENKO, SERGEY; POHRIBNYAK, DARYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The range of obstacles that hinder the development of digital transformations in Ukraine is characterized: institutional, infrastructural, ecosystem. The chronology of the development of accounting practice in the context of industrial revolutions is given and the main management goals and tasks of accounting that arise as a result are defined in their context. The problematic issues in the theoretical and practical plane of accounting are summarized in the works of scientists, in particular: actualization of the digital accounting paradigm, research of factors inhibiting the development of digital accounting in the country, formation of digital asset accounting methods, change and addition of accounting principles, development of competencies and features training of an accountant, IT-modernization of accounting. The usefulness of using digital capabilities in the field of accounting and taxation is substantiated. The discrepancy between domestic accounting practice and international standards, which is becoming increasingly important in the context of globalization and business integration, is described. The concepts of organization accounting and analytical support, accounting and analytical system and accounting and information support in the context of digitalization are substantiated and the reasons for changes in their functional impact in relation to information are highlighted. Aspects that characterize the changes in the functional impact in relation to information are substantiated. There is a loss of functionality of paper media, accumulation and distortion of information in the electronic space with further complication of the processes of its processing and analysis, increasing the risk of information leakage with the need to strengthen economic security measures of the business entity, etc. The need to form a new methodological basis for the identification, evaluation and accounting of new objects that arise in the context of digitalization. The growth of the role of accounting information for the management of enterprises in modern conditions is noted.